Oxidation of Secondary Benzylic Alcohols to Ketones and Benzylic Oxygenation of Alkylarenes with Hydrogen Peroxide in the Presence of Activated Carbon - Nishida, Shunsuke; Hayashi, Masahiko (Synlett, 2012)
A variety of benzylic alcohols were oxidized to the corresponding carbonyl compounds selectively with 30% hydrogen peroxide (H2O2) in the presence of activated carbon. Alkylarenes such as fluorenes, xanthenes, and anthrone were also effectively oxygenated to the corresponding carbonyl compounds with 30% H2O2 as oxidant in the presence of activated carbon.
Keywords: oxidation; benzylic alcohol; hydrogen peroxide; activated carbon; fluorene